2015
DOI: 10.1097/meg.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of FibroMeter VCTE for hepatic fibrosis in patients with nonalcoholic fatty liver disease

Abstract: Our preliminary findings indicate that FibroMeter VCTE is superior to both NFSA and TE for the diagnosis of severe fibrosis in patients with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…Of the serum-based diagnostic tests, we found that complex scores show better accuracy than simple scores. Previous individual studies support these findings in general NAFLD populations (52,53,55). In our meta-analysis, both the NFS and BARD had average, and often poor, pooled sensitivities and specificities, with high heterogeneity.…”
Section: Discussionsupporting
confidence: 85%
“…Of the serum-based diagnostic tests, we found that complex scores show better accuracy than simple scores. Previous individual studies support these findings in general NAFLD populations (52,53,55). In our meta-analysis, both the NFS and BARD had average, and often poor, pooled sensitivities and specificities, with high heterogeneity.…”
Section: Discussionsupporting
confidence: 85%
“…The FibroMeter tests include the FibroMeter VCTE which is a combination of blood markers with the Fibroscan result (Echosens) in a single formula (Table S1 and Table ). Recent studies have demonstrated that the combinatory FibroMeter VCTE outperforms blood fibrosis tests and Fibroscan for the non‐invasive evaluation of liver fibrosis in NAFLD . Used as second‐line procedure after blood fibrosis tests or Fibroscan, the FibroMeter VCTE decreases the rate of patients with undetermined diagnosis by twofold …”
Section: Discussionmentioning
confidence: 99%
“…Another FibroMeter model named FM VCTE has been developed for hepatitis C virus patients by combining clinical and biological parameters together with liver stiffness by transient elastography . In a pilot study of 52 NAFLD patients, FM VCTE detected severe fibrosis with a higher accuracy than transient elastography alone …”
Section: Introductionmentioning
confidence: 99%
“…16 In a pilot study of 52 NAFLD patients, FM VCTE detected severe fibrosis with a higher accuracy than transient elastography alone. 17 With this background, we aimed to evaluate the diagnostic performance of transient elastography, FM NAFLD, and FM VCTE in fibrosis staging in NAFLD patients and to compare their performances with other scores for fibrosis. We also tested the hypothesis that the use of FM VCTE could resolve diagnostic uncertainties in patients with inconclusive FibroScan results.…”
Section: Introductionmentioning
confidence: 99%